Characterization of active lead molecules from Lissocarinus orbicularis with potential antimicrobial resistance inhibition properties - Sekar Harikrishnan; Murugan Parivallal; Mohamad S. Alsalhi; Shanmugam Sudarshan; Narenkumar Jayaraman; Sandhanasamy Devanesan; Aruliah Rajasekar; Singaram Jayalakshmi (Elsevier, 2021)
Background: Marine organisms are the potential contributors of novel bioactive molecules. Nevertheless, their biodiversity and the versatility of bioactive metabolites have not been fully explored. Hence, the aim of the present study was to investigate the potentials of gut associated bacteria from a marine crab for the production of novel antibacterial compound. Methods: Aerobic gut autochthonous bacteria isolated from marine crab (Lissocarinus orbicularis) collected from Pazhayar coastal area in Nagapattinam district of Tamil Nadu, India were screened for antibacterial activity. Optimization for bacterial growth and antimicrobial compound production, extraction, purification and characterization were studied. Results: In the present study, eight morphologically distinct colonies of L. orbicularis gut associated aerobic bacterial isolates (Iso1-Iso8) on Zobell marine agar plate were selected. Isolates were screened for antimicrobial activity against human bacterial pathogens such as Salmonella paratyphi, Vibrio cholera, Vibrio parahaemolyticus, Aeromonas hydrophila and Listeria monocytogenes. On the basis of screening results, isolate 5 (Iso5) was selected as the most potential strain and identified as Paenibacillus polymyxa using biochemical and 16S rRNA sequencing methods. The sequence data was submitted to NCBI (Gene bank Accession No: MK583465). Optimization of P. polymyxa for growth and antimicrobial compound production revealed incubation period (36 h), agitation (150 rpm), pH 8.0, 35 °C, 2.5% salinity, 2% glucose and 1% yeast extract as carbon and nitrogen sources respectively were the ideal conditions and mass culture was done with these parameters. Antimicrobial compound from the cell free supernatant of mass culture medium was extracted using ethanol. The lowest minimum inhibitory concentration (MIC) of 16 μg/ml was observed against of both V. parahaemolyticus and V. cholerae. GC-MS analysis of the active ethanol fraction showed the presence of different components such as dodecane (96.72%), Tridecane (1.69%), Undecane, 2,6-dimethyl- (1.69%), Tetradecane (1.12%) and Dodecane, 2,6,11-trimethyl- (1.12%). Conclusion: The present study showed that the gut associated autochthonous bacteria of marine crabs are one of the potential sources of antibacterial compound. However, further studies are needed for the identification of the antimicrobial compound.